Control software development of COD sensor - You, Jia. (2009)
Chemical Oxygen Demand (COD) which measures the oxygen demand of bio-gradable pollutants plus the oxygen demand of non-biodegradable oxidizablle pollutants. It is considered to be one of the most important parameters in wastewater and waste chemical treatment processes. However, the determination of COD is very difficult and time consuming which needs at least 2 hours by the standard method. Therefore, a lot of research has been conducted to develop a simple, accurate, yet fast COD determination method to help the environmental monitoring and control. There are some methods to be automated among all the research in this direction. Each measurement method is discussed in terms of their advantages and disadvantages. For improving the conventional method, a new COD sensor is proposed. Ozone has several suitable chemical properties for the new COD sensor is proposed. Ozone is easily obtained form the ambient air. Ozone has strong oxidation agent so it can be proposed as substitute to KMnO4 or K2CrO7 in standard methods. An electronic means of ORP sensor can monitor the concentration of ozone in the water. The development of the proposed COD sensor is introduced on both hardware and software design. The control software of COD sensor is developed for implement the COD sensor. The control software development is presented in this thesis. Because of the portable, fully automated, and fast in determining COD values is expected by the new system. It can be used for on-line COD monitoring. Due to the high demand for portable online COD meter on the market, there is a very high potential to commercialize the product.